PENGARUH PENGGUNAAN THINK PAIR SHARE (TPS) MELALUI KEAKTIFAN BELAJAR TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP - Putra Wahidin M.; M. Yusuf T; Andi Dian Angriani (Faculty of Tarbiyah and Teacher Training, 2019)
This study aims to find out about the influence of the Think Pair Share model on subjects of a linear variable system of variables in class VII of SMPN 2 Balocci. This type of research is a quasi experiment with factorial design and treatment design by 2x2 level. The population in this study were all students of class VII at SMPN 2 Balocci, totaling 120 people. The sample in this study was class VII1 as an experimental class and class VII2 as a control class. The research instrument used in this study was a test of concept comprehension ability and a mathematical representation ability test. Based on the results of research conducted on the experimental class and the control class, it was found that (1) Learning using the TPS model for the experimental class the post test value was far better than the pre test value ie the maximum post test value was 88 while in the control class the maximum post test value 85; (2) mathematical communication skills in the experimental class post test results the category is better than the control class, (3) learning activity in the experimental class the category is better than the control class. The conclusion of the results of the study is that there is a significant difference between TPS and conventional methods on the mathematical communication skills of Grade VII students of SMPN 2 Balocci, that learning with the TPS model is more effective in increasing students' mathematical communication abilities than conventional methods. There is also an influence of interaction between learning models in terms of learning activeness towards mathematical communication skills of Grade VII students of SMPN 2 Balocci. AbstrakPenelitian ini bertujuan untuk mengetahui tentang pengaruh model Think Pair Share pada mata pelajaran sistem persamaan liniear satu variabel pada kelas VII SMPN 2 Balocci. Jenis penelitian yang digunakan adalah quasi experiment dengan desain factorial desain dan rancangan penelitian treatment by level 2x2. Populasi pada penelitian ini adalah seluruh peserta didik kelas VII SMPN 2 Balocci yang berjumlah 120 orang. Sampel pada penelitian ini adalah kelas VII1 sebagai kelas eksperimen dan kelas VII2 sebagai kelas kontrol. Instrumen penelitian yang digunakan dalam penelitian ini adalah tes kemampuan pemahaman konsep dan tes kemampuan representasi matematis. Berdasarkan hasil penelitian yang dilakukan terhadap kelas eksprimen dan kelas kontrol, diperoleh bahwa (1) Pembelajaran menggunakan model TPS untuk kelas eksperimen nilai post test jauh lebih baik dari pada nilai pre test yaitu nilai maksimum post test adalah 88 sedangkan pada kelas kontrol nilai maksimum post test 85;(2) kemampuan komunikasi matematis pada hasil post test kelas eksperimen kategorinya lebih baik dibanding kelas kontrol;(3) keaktifan belajar pada kelas eksperimen kategorinya lebih baik dari pada kelas kontrol, Kesimpulan hasil penelitian adalah terdapat perbedaan yang signifikan antara TPS dan metode konvensional terhadap kemampuan komunikasi matematis siswa kelas VII SMPN 2 Balocci, yaitu pembelajaran dengan model TPS lebih efektif meningkatkan kemampuan komunikasi matematis siswa daripada metode konvensional dan juga terdapat pengaruh interaksi antara model pembelajaran ditinjau dari keaktifan belajar terhadap kemampuan komunikasi matematis siswa kelas VII SMPN 2 Balocci.